Cytokine Profiles Associated With Worse Prognosis in a Hospitalized Peruvian COVID-19 Cohort - Pons, Maria J.; Ymaña, Barbara; Mayanga-Herrera, Ana; Sáenz, Yolanda; Alvarez-Erviti, Lydia; Tapia-Rojas, Salyoc; Gamarra, Roxana; Blanco, Amanda B.; Moncunill, Gemma; Ugarte-Gil, Manuel F. (Frontiers in Immunology, 2021)
Background In the most severe forms of SARS-CoV-2 infection, large numbers of innate and adaptive immune cells become activated and begin to produce pro-inflammatory cytokines, establishing an exacerbated feedback loop of inflammation. Methods: A total of 55 patients with laboratory-confirmed COVID-19 admitted to the Hospital Nacional Guillermo Almenara Irigoyen in Lima, Peru were enrolled during August-October 2020. Of these, 21 had moderate disease, 24 severe diseases and 10 died. We measured 30 cytokines and chemokines by quantitative suspension array technology and anti-spike IgG antibodies using a commercial ELISA. We evaluated these parameters in peripheral blood every 2-5 days until patient discharge or death. Patient information and clinical parameters related were obtained from the respective clinical histories. Results: The frequency of obesity differed among the 3 groups, being most frequent in patients who died. There were also significant differences in clinical parameters: hemoglobin, segmented neutrophils, lymphocytes, C-reactive protein, creatinine and D-dimer levels. Greater anti-spike IgG antibody concentrations were associated with fatal outcomes. In univariate analyses, higher baseline concentrations of IL-6, MIP-1α, GM-CSF, MCP-1, IL-15, IL-5, IL1RA, TNFα, IL-8 and IL-12p70 correlated with severity, while multivariable analysis showed that increased concentrations in 4 biomarkers (GM-CSF, MCP-1, IL-15, IL-8) were associated with fatal outcomes. Longitudinal analysis showed IL-6 (hazard ratio [HR] 6.81, 95% confidence interval [CI] 1.6-28.7) and MCP-1 (HR 4.61, 95%CI 1.1-19.1) to be related to mortality in hospitalized COVID-19 patients. Conclusions: Cytokine, chemokine and growth factor profiles were identified and validated related to severity and outcomes of COVID-19. Our findings may be useful to identify novel criteria for COVID-19 patient stratification at hospital entry.